1993
DOI: 10.1111/j.1432-1033.1993.tb18259.x
|View full text |Cite
|
Sign up to set email alerts
|

The amino acid sequence of human ribonuclease 4, a highly conserved ribonuclease that cleaves specifically on the 3′ side of uridine

Abstract: . (1986a) Biochemistry 25,7255-72641 was purified from human plasma and its amino acid sequence was determined. This protein is a 119-residue single-chain polypeptidc cross-linked by four disulfide bonds and has an amino-terminal pyroglutaminyl residue. No post-translational modifications were observed during extensive sequence studies on peptide fragments, except for the amino-terminal pyroglutamic acid and a possible deamidation of Asn66. The protein is homologous to the pancreatic ribonucleases and angioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
54
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 69 publications
0
54
1
Order By: Relevance
“…Our results showed that the specificity of UpG was higher than that of CpG, confirming the nature of RNase-4. The singular specificity of this RNase has been reported to have a marked preference for uridine compared with cytidine, in contrast to the more general pyrimidine specificity of other ribonucleases such as rnase-1, -2, -3 and angiogenin (5). The kinetic constant obtained was lower than that reported in the literature for human and porcine rnase-4 (4).…”
Section: Resultscontrasting
confidence: 53%
See 2 more Smart Citations
“…Our results showed that the specificity of UpG was higher than that of CpG, confirming the nature of RNase-4. The singular specificity of this RNase has been reported to have a marked preference for uridine compared with cytidine, in contrast to the more general pyrimidine specificity of other ribonucleases such as rnase-1, -2, -3 and angiogenin (5). The kinetic constant obtained was lower than that reported in the literature for human and porcine rnase-4 (4).…”
Section: Resultscontrasting
confidence: 53%
“…it is a ubiquitous enzyme and is present in the highest amounts in the liver and lungs (4). a salient feature of rnase-4, which distinguishes it from other rnases, is its high interspecies similarity (90%), which strongly suggests that it performs a more specialized function than simply digesting or 'cleaning up' RNA (5). It was first isolated from bovine tissues in 1987, at which time it was called rnase Bl4 (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acid analyses were performed by the phenylisothiocyanate-precolumn-derivatization method (Bidlingmeyer et al, 1984) as described (Zhou and Strydom, 1993). Sequencing studies employed a Beckman 890 M sequencer .…”
mentioning
confidence: 99%
“…When there is no activating stimulus present, the RNase L protein exists in a latent, catalytically inactive monomeric form and is bound by an inhibitory protein (RLI) (Bisbal et al 1995). However, upon binding 5'-triphosphorylated-2'-5'-A synthetase molecules, the protein forms a dimerized structure that activates the cytosolic endoribonucleolytic domain (Zhou et al 1993). In mammalian cells, activation of the RNase L protein leads to cell death via an apoptotic pathway (Pandey and Rath 2004).…”
mentioning
confidence: 99%